Seismic performance of bridges with novel SMA cable‐restrained high damping rubber bearings against near‐fault ground motions - Fang, Cheng; Liang, Dong; Zheng, Yue; Lu, Shiyuan (Earthquake engineering & structural dynamics, 2022)
This study presents a novel type of shape memory alloy (SMA) cable‐restrained high damping rubber (SMA‐HDR) bearing, which is particularly suited to near‐fault (NF) regions where the pulsing effect potentially exists in the ground motions. The working mechanism of the bearing is first described, followed by an experimental investigation on a full‐scale SMA‐HDR bearing specimen. The test results confirm the efficient restraining effect offered by the SMA cables, which contribute to 65% and 24.4% of the lateral load resistance and total energy dissipation, respectively, prior to the initial fracture of the SMA cables. The failure of the cables is initiated near the end grip where moderate stress concentration exists at this region. Following the experimental study, the numerical modeling strategy for the bearing is discussed, and a case study is then presented, demonstrating the application of the SMA‐HDR bearings in the Datianba #2 highway bridge, a real project that first adopts the proposed bearings in the world. A simplified design process is introduced for the bridge with novel SMA‐HDR bearings to mitigate the potential damage during strong earthquakes especially the NF ones. The system‐level analysis on the prototype bridge shows that the novel SMA‐HDR bearings equipped with ten 7×7×1.2 SMA cables in each bearing could reduce the average maximum bearing displacement (MBD) by nearly 30% compared with the conventional bridge with HDR bearings. The application of the novel SMA‐HDR bearing can significantly alleviate the pounding effect, especially under the NF earthquakes. The presence of the SMA cables tends to increase the maximum force response of the piers, but this effect is minor and under control.